Aesthetics of everyday life : east and west - Yuedi, Liu; Carter, Curtis L. (Cambridge Scholars Publishing, 2014)
As a new trend in aesthetics appearing concurrently in the West and the East in the last ten years, the aesthetics of everyday life points to a growing diversification among existing methodologies for pursuing aesthetics, alongside the shift from art-based aesthetics. The cultural diversity manifest in global aesthetics offers common ground for the collaborative efforts of aesthetics in both the West and the East. Given the rapidly growing interest and its potential for attracting new audiences extending beyond the more narrowly focused traditions of twentieth-century analytic and environmenta.